2021
DOI: 10.1007/s11325-021-02506-w
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits are associated with subjective sleep quality outcomes among university students: findings of a cross-sectional study

Abstract: Purpose This study investigated the relationships between eating habits and sleep quality among university students. Methods In a cross-sectional study, university students completed a self-report questionnaire to assess eating habits and meal timing. We assessed subjective sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and examined the associations between eating habits and overall sleep quality and its components. Results Four hundred ninety-eight students participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
0
15
1
1
Order By: Relevance
“…The relatively low prevalence of good sleep quality (about 17%) among our university students is also consistent with and mirrors for other reports in the UAE and other parts of the globe. However, this number is lower than previous estimates among students in the UAE, whereby the prevalence rates of good sleep, using similar assessment tools were 34% in 2020 and 44.8% in 2021, respectively ( 50 , 76 ). Such a high heterogeneity in the reported prevalence of sleep quality among students in the same institute during two consecutive years is a mirror for the wide spectrum of interacting and interplaying variables impacting sleep quality, and the high sensitivity of sleep quality for variable environmental (dietary and lifestyle) factors.…”
Section: Discussioncontrasting
confidence: 62%
“…The relatively low prevalence of good sleep quality (about 17%) among our university students is also consistent with and mirrors for other reports in the UAE and other parts of the globe. However, this number is lower than previous estimates among students in the UAE, whereby the prevalence rates of good sleep, using similar assessment tools were 34% in 2020 and 44.8% in 2021, respectively ( 50 , 76 ). Such a high heterogeneity in the reported prevalence of sleep quality among students in the same institute during two consecutive years is a mirror for the wide spectrum of interacting and interplaying variables impacting sleep quality, and the high sensitivity of sleep quality for variable environmental (dietary and lifestyle) factors.…”
Section: Discussioncontrasting
confidence: 62%
“…The opposite trend showed by melatonin, with the low FIS considering it more effective than the high FIS did, could be related to its chronobiotic function, regulating sleep, energy metabolism, and anti-inflammatory effects [ 66 ]. Bad dietary habits, as the low FIS group showed, were associated with sleep disorders [ 67 ]; thus, low FIS could be more interested in melatonin and trust its beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of subgroup analysis showed that the association between skipping breakfast and hypertension was consistent in studies with and without adjustment of BMI, suggesting that the association could not be fully explained by the factor of overweight/obesity. In addition, skipping breakfast may be a behavioral marker of a cluster of unhealthy lifestyles, such as poor dietary habit, low physical activity, and irregular sleeping [ 33 , 34 ], all of which may expose the participants to a higher risk of hypertension. Besides, habitual breakfast skipping is associated with higher levels of systematic inflammatory markers such as C-reactive protein [ 35 ] and glycoprotein acetyl [ 36 ], which may suggest chronic inflammation as a possible molecular basis for the association between skipping breakfast and hypertension.…”
Section: Discussionmentioning
confidence: 99%